Bovine campylobacteriosis in heifer: pathogenesis study and insights in the conventional and molecular diagnosis in an experimental bovine model and field cases - Garcia, Juan Agustin; Farace, Pablo Daniel; Gioffre, Andrea; Romeo, Florencia; Verna, Andrea Elizabeth; Mendez, Maria Alejandra; Morsella, Claudia Graciela; Aller Atucha, Juan Florencio; Signorini Porchiett, Marcelo Lisandro; Paolicchi, Fernando (Springer Nature, 2024)
Campylobacter fetus spp. is a bacterium associated to reproductive losses in cattle worldwide. It is a venereal infectious disease known as bovine campilobacteriosis, with high impact mainly in countries with extensive production systems. Here, we show pathogenesis and diagnostic methods for Campylobacter fetus detection in cervico-vaginal mucus (CVM) samples from heifers experimentally infected and field cases from herds with low reproductive performance by campylobacteriosis infection. Bacterial culture, direct immunofluorescence test and qPCR were used as diagnostic methods to evaluate detection of C. fetus. In the experimental model 30 Aberdeen Angus and crossbred heifers and 4 Aberdeen Angus bulls for natural mating were assigned to 3 groups experimentally challenged with C. fetus subsp. fetus (Cff), C. fetus subsps venerealis (Cfv) and C. fetus subsp venerealis biovar intermedius (Cfvi), respectively, and a negative control group, all followed for 9 months. Also, field samples of CVM and aborted fetuses were recollected from seven beef cattle farms. Bacteriological culture had the higher C. fetus detection rate in CVM being the most appropriate, followed by qPCR (with commercial extraction DNA kit), direct immunofluorescence test and qPCR (with in-house extraction DNA method), in both, experimental model and field cases. From experimental model after natural mating, 62.5% and 25% heifers got pregnant from Cff and Cfvi groups, respectively, while from Cfv no pregnancy was detected. The strain more frequently detected was Cfvi, followed by Cff and Cfv. Colonization of Cff in female genital tract with high number of carriers and presence in aborted fetuses was evidenced, suggesting a high risk to bovine reproductive health. Bacteriemia was not detected after genital infection. Given the low detection rate of either test, we suggest the use of both, PCR based methods and bacterial culture could result in higher detection rate in farms with endemic campylobacteriosis.